Resiliency and loss: A case study of two clusters of high elevation ice patches in the Greater Yellowstone ecosystem, USA - Reckin, Rachel (Archaeological Review from Cambridge, 2017)
Archaeologists worldwide know very little about the immense ecosystem changes already underway in the mountains and the threats that anthropogenic climate change poses to high elevation cultural resources. So how do we proceed? What do we prioritize? Is high elevation ice resilient to these changing climates, and if so, how much? How much time do we have before mid-latitude high elevation ice disappears entirely? This paper comments on the impacts of climate change to high elevation cultural resources, particularly ice patches, whose presence as a constant source of water is vital to the general appeal of high elevations for human occupation. Beyond their ecological importance, ice patches can also preserve ancient organic artifacts and paleobiological material for over 10,000 years. And they are melting rapidly thanks to anthropogenic climate change. This paper offers a case study of two groups of archaeologically productive high elevation ice patches from the Greater Yellowstone Ecosystem, analyzing their resiliency in the face of warming temperatures and changing climates. Ultimately, I conclude that high elevation patches of ice and snow may be losing their resiliency to warmer temperatures as their ancient ice melts, making them ever more vulnerable to climate change. Ice patch researchers are in a race against time to identify productive ice patches and recover any fragile artifacts or paleobiological material they may contain before they melt completely. For many of these patches, this would be their first complete melt since the early Holocene.
Keywords: climate change; high elevation archaeology; ice patch archaeology; glacial archaeology; cryosphere; paleoclimate